Comparing profitability of Burlina and Holstein Friesian cattle breeds - Martino Cassandro; Chiara Dalvit; Massimo De Marchi; Denis Pretto (Italian Journal of Animal Science, 2010)
Aim of this study was to compare profitability of Burlina and Holstein Friesian cows in northern Italy. Cow’s profitability was calculated for each breed, with consideration of economic incentive programs and alternative milk pricing scenarios. The difference in annual profitability between Burlina and Holstein Friesian ranged from −€719 to −€274 per cow per year. In a low-input management level with a cow’s incentive payment and a specific cheese market strategy the low milk yield of Burlina can be compensate respect to Holstein Friesian.